2024
DOI: 10.1186/s12889-023-17473-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intentions to receive monkeypox vaccine. A systematic review and meta-analysis

Darwin A. León-Figueroa,
Joshuan J. Barboza,
Mario J. Valladares-Garrido
et al.

Abstract: Background Immunization, as a preventive strategy against infectious diseases, has consolidated its position as a fundamental pillar in the field of public health. Therefore, the present study aimed to determine the prevalence of the intention to receive the monkeypox (Mpox) vaccine. Methods A systematic review and meta-analysis of the available evidence was performed using five databases (PubMed, Scopus, Web of Science, Embase, and ScienceDirect) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…The effectiveness and safety of mpox vaccine have been confirmed by several studies [ 9 , 10 ]. Based on the results of our review and the study by León-Figueroa et al [ 58 ], people who were confident in the safety and efficacy of the mpox vaccine were more likely to be vaccinated. Therefore, experts should develop and promote a global consensus on mpox vaccination.…”
Section: Discussionmentioning
confidence: 84%
“…The effectiveness and safety of mpox vaccine have been confirmed by several studies [ 9 , 10 ]. Based on the results of our review and the study by León-Figueroa et al [ 58 ], people who were confident in the safety and efficacy of the mpox vaccine were more likely to be vaccinated. Therefore, experts should develop and promote a global consensus on mpox vaccination.…”
Section: Discussionmentioning
confidence: 84%
“…A meta-analysis of 29 studies involving 52,658 participants demonstrated that the pooled prevalence of the intention to vaccinate against mpox was 61% around the world [ 10 ]. However, people’s willingness to receive mpox vaccination does not guarantee that they will get vaccinated [ 11 ].…”
Section: Introductionmentioning
confidence: 99%